Association between Functioning and Dynamics in Families of Children with ADHD in Pakistani Context: Functioning and Dynamics in Families of Children with ADHD - Rajput, Aatir Hanif; Dahri, Sajida; Baloch, Fozia; Channa, Summaira; Ahmed, Shahzad; Ansari, Moin Ahmed; Hyder, Fezan (Pakistan Journal of Health Sciences, 2025)
Attention-Deficit/Hyperactivity Disorder (ADHD) affects multiple aspects of a child’s development, including family dynamics. Understanding the association between family functioning and ADHD can provide insights into its social determinants. Objectives: To evaluate family functioning and dynamics in families of children with ADHD and compare them with healthy controls. Methods: A comparative cross-sectional study was conducted at the Child Psychiatry Clinic, Liaquat University Hospital, Hyderabad, from August 2024 to January 2025. A total of 120 participants (60 ADHD cases and 60 age-matched controls) were recruited using non-probability consecutive sampling. Family structure, socioeconomic status, parental employment, education, and family discord were assessed through structured interviews. Data were analyzed using SPSS version 25.0. Results: Family dysfunction was significantly associated with nuclear family structure (39.2% vs. 88.9%, p=0.044), lower socio-economic status (41.2% vs. 11.1%, p=0.031), and maternal educational level (33.3% vs. 11.1%, p=0.038). Additionally, a history of parental/family discord was significantly more prevalent in families with dysfunction (52.9% vs. 11.1%, p=0.005). Conclusions: It was concluded that family discord is significantly associated with ADHD, highlighting the need for family-based interventions. Addressing family conflict may help improve outcomes for children with ADHD.